Playground contamination by potentially pathogenic bacteria: a systematic review - Reis, Catarina (2025)
Playgrounds are public spaces that offer recreational opportunities for hundreds of people, including children, young people, adults, and the elderly. Numerous pathogenic bacteria have been described in the literature as etiologic agents of several infections, with distinct manifestations and clinical outcomes, particularly affecting children's health. This systematic review aims to perform a scoping review of the state of the art regarding playground contamination by potentially pathogenic bacteria and associated public health concerns. An extensive search was conducted in PubMed and Web of Science, applying predefined inclusion and exclusion criteria and described in a flow diagram of the methodology according to PRISMA 2020 Checklist standards. After quality assessment, 4 scientific articles were included and data was extracted. Two studies from the USA and Poland focused on the identification of bacteria in sandboxes, one study from Hungary accessed playground surfaces, and in a study from Mexico, authors analyzed bacteria prevalence on children's hands and toys in playgrounds. Data analysis demonstrated the presence of potentially pathogenic bacteria in playgrounds in different sampling areas, highlighting a public health issue and raising awareness about the hygiene conditions of the infrastructures and the importance of hand hygiene for those who frequent them. Further research, in a global scale, is crucial to properly access overall pathogenicity levels in these locations, particularly on surface areas where there is still limited information in the literature and to perform an accurate risk assessment.